Effectiveness of Local Government Information System on Planning Document Preparation at the BPBD of Pasangkayu Regency - Andi Fitrianti; Muhammad Amri; Nurlinah (Journal of Public Administration and Government, 2023)
The Local Government Information System is a system that documents, administers, and processes local development data into information that is presented to the public and used as decision-making material in the context of planning, implementation, and evaluation of local government performance. The research aims to determine the effectiveness of RGIS and support its utilization. A qualitative method with a descriptive analytic approach is used in analyzing this research to get in-depth data and data that contains meaning. The results show that RGIS is very effective as a joint program between the Central Government and local governments, where the completeness, currency, accuracy, and validity of data are important elements in the process of collecting and inputting data elements, which will then be further processed to produce data analysis in the RGIS application, and the support and commitment of the local government for its utilization and development.